2022
DOI: 10.15388/infedu.2023.12
|View full text |Cite
|
Sign up to set email alerts
|

A Second Experimental Study the Application of a Teaching Plan for the Algorithms Subject in an Undergraduate Course in Computing using Active Methodologies

Abstract: The contents taught in the programming subjects have a great relevance in the formation of computing students. However, these subjects are characterized by high failure rates, as they require logical reasoning and mathematical knowledge. Thus, establishing knowledge through the subject of algorithms can help students to overcome these difficulties and absorb the contents and skills required. Thus, this work aims to present and discuss the results of a second experiment on the application of a teaching plan com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…A study conducted by Da Silva et al [32] presents an implementation of a teaching plan for an algorithms course using active methodologies like virtual learning environments, Coding Dojo, gamification, problem-based learning, flipped classroom, and serious games. These were chosen to teach algorithms to university computer science students and evaluated by experts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study conducted by Da Silva et al [32] presents an implementation of a teaching plan for an algorithms course using active methodologies like virtual learning environments, Coding Dojo, gamification, problem-based learning, flipped classroom, and serious games. These were chosen to teach algorithms to university computer science students and evaluated by experts.…”
Section: Resultsmentioning
confidence: 99%
“…Another active methodology recorded in the studies analyzed is the flipped classroom, supported by the use of ICT with virtual platforms and in works such as those by [32,33,36]; it is used as a complement to problem-based learning. Thus, it is identified that it benefits students' academic performance in terms of improvements in grades and an increase in the number of students passing [33,34,36] and greater effort and participation [34,36].…”
Section: Flipped Classroommentioning
confidence: 99%
“…When it comes to teaching computing, several studies relate positive results in the application of differentiated methodologies inside classroom [5,7,18].…”
Section: The Use Of Active Methodologies In the Teachingmentioning
confidence: 99%
“…Garcia and Oliveira et al [18] applied a teaching strategy in the teaching of Algorithms, which involved several active methodologies (such as gamification, TBL, PBL, and virtual learning environments, among others) and concluded that there were advances in student learning when compared to traditional teaching methods.…”
Section: The Use Of Active Methodologies In the Teachingmentioning
confidence: 99%
“…Does he have time to learn how to use it? Although secondary studies have been conducted to examine publications analyzing the adoption of ALMs ( de Andrade et al (2021), Garcia et al (2022), Suarez-Escalona et al (2022), Ahshan (2021)), they have not centered explicitly on identifying suitable methodologies to aid educators in teaching programming at the higher education level, nor have they proposed a collaborative and open repository to support programming instructors. Through an SMS, we can compile the factors that may bolster programming teaching and ascertain which ALMs have been embraced, enabling educators to implement these methodologies in their classrooms.…”
Section: Introductionmentioning
confidence: 99%